2021
DOI: 10.2147/rmhp.s311074
|View full text |Cite
|
Sign up to set email alerts
|

The Willingness to Receive COVID-19 Vaccine and Its Associated Factors: “Vaccination Refusal Could Prolong the War of This Pandemic” – A Systematic Review

Abstract: Background The outbreak of coronavirus disease 2019 (COVID-19) in Wuhan, China, spreads globally, since its declaration by the World Health Organization (WHO) as a COVID-19 pandemic on March 11, 2020. COVID-19 vaccine is a crucial preventive approach that can halt this pandemic. The present systematic review was aimed to assess the level of willingness to receive COVID-19 vaccine and its associated factors. Methods A comprehensive literature search was conducted by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
246
2
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(285 citation statements)
references
References 102 publications
(264 reference statements)
26
246
2
11
Order By: Relevance
“…A recent systematic review on vaccine hesitancy suggested that willingness to receive the COVID-19 vaccine ranged from 27.7 to 91.3% across the world ( 2 ). Further, age, educational status, trust in healthcare and health insurance have all been associated with willingness to receive the COVID-19 vaccine ( 2 4 ). The goal of the current study was to clarify the proportion of the population likely to decline a COVID-19 vaccine and the associated reasons.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review on vaccine hesitancy suggested that willingness to receive the COVID-19 vaccine ranged from 27.7 to 91.3% across the world ( 2 ). Further, age, educational status, trust in healthcare and health insurance have all been associated with willingness to receive the COVID-19 vaccine ( 2 4 ). The goal of the current study was to clarify the proportion of the population likely to decline a COVID-19 vaccine and the associated reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the increased willingness of physicians to be vaccinated suggests, as probably expected, that approval of vaccination will vary depending on the social status, the profession and other factors. This suggests that, in order to increase the approval of vaccination, HCWs and the society in general should be approached also in a structured and individualized manner, through political decisions regarding educational interventions in the workplace, media coverage, and maybe societal benefits for vaccinated individuals [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…4) 60,61 . Smaller studies (n < 1,000) were more likely to increase the heterogeneity of the results, so following the example of Robinson et al 24 , the authors chose to restrict the subgroup analysis to larger studies which may have had more robust estimates of vaccine acceptance.…”
Section: Time Of Surveymentioning
confidence: 99%
“…Since the beginning of the COVID-19 pandemic, several systematic reviews have been conducted into COVID-19 vaccine uptake and adherence [20][21][22][23][24] .…”
mentioning
confidence: 99%
See 1 more Smart Citation